2021
DOI: 10.54029/2021zfv
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine usage amongst multiple sclerosis patients in Iran

Abstract: Objectives: The aim of this study was to determine the prevalence and patterns of complementary and alternative medicine (CAM) usage amongst multiple sclerosis (MS) patients in Iran and to evaluate the perceived effectiveness. Methods: This was a descriptive cross-sectional study. Data were collected from 194 patients with MS at the neurology clinics affiliated with Shiraz University of Medical Sciences by a semi-structured questionnaire. Results: The prevalence of CAM usage was 67.9%. Herbal medicine was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 30 On the contrary, herbal medicine constituted the predominant choice among Iranian MS patients, accounting for 64.2% of CAM use. 33 These findings diverge from a systematic review of CAM recommendations for depression, which identified exercise as the most recommended intervention for depression treatment while advising against the use of omega-3 fatty acids and vitamin D. 41 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 30 On the contrary, herbal medicine constituted the predominant choice among Iranian MS patients, accounting for 64.2% of CAM use. 33 These findings diverge from a systematic review of CAM recommendations for depression, which identified exercise as the most recommended intervention for depression treatment while advising against the use of omega-3 fatty acids and vitamin D. 41 …”
Section: Discussionmentioning
confidence: 95%
“…This study included data on the use of CAMs among patients with NMOSD and MOGAD, which had not been widely reported, unlike other studies, which focused mainly on MS patients. 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CAM use also varied among specific disease populations, such as patients with diabetes mellitus (ranging from 37 % to 86 %), multiple sclerosis (67.9 %–85 %), dyslipidemia (77.4 %), thalassemia (68 %), coagulation disorders (49.3 %), cancer (35 %), and dermatological diseases (31 %). These differences in CAM use may be attributed to cultural factors, availability of CAM modalities, and the health status of individuals [ 23 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. Anbari and Ghanadi [ 38 ] reported a lifetime CAM use of approximately 80 % among clients over 15 years old referred to health centers and hospitals in Khorramabad .…”
Section: Discussionmentioning
confidence: 99%